Sustainability in vocational education and training - national and international experiences - Hermann, Ralf [Herausgeber]; Kress, Hannelore [Herausgeber]; Olesen, Julia [Herausgeber] (Bundesinstitut für Berufsbildung, 2024)
"The publication highlights the global prioritization of integrating sustaina ble development into technical education and vocational training (TVET). It documents the evolving discourse on sustainability in TVET and emphasizes the diversity of approaches among countries while recognizing common goals. GOVET‘s (German Office for International Cooperation in VET) initiatives include organizing study tours and bilateral workshops, facilita ting exchanges on sustainability in vocational education. The publication emphasizes the relevance of sustainability in addressing global challenges like climate change and it aims to provide a platform for international discussions, encompassing macro to micro levels of TVET, showcasing expe riences and best practices from Brazil, Colombia, Costa Rica, Ghana, Kenya, Mexico, South Africa, Uzbekistan, Zambia, Zimbabwe and Germany." (Editor, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; G 2.5 Nachhaltigkeit; I 2.1 Deutschland; I 2.3.1 Afrika; I 2.3.3 Lateinamerika; I 2.3.4 Asien; 370; Berufsbildung; Nachhaltige Entwicklung; Green skills / Grüne Kompetenzen; Internationale Zusammenarbeit; Best practice; Brasilien; Bundesrepublik Deutschland; Costa Rica; Ghana; Kenia; Kolumbien; Lateinamerika; Mexiko; Simbabwe; Südafrika; Usbekistan